The Brewer‐Dobson Circulation During the Last Glacial Maximum. Issue 5 (29th February 2020) - Fu, Qiang; White, Rachel H.; Wang, Mingcheng; Alexander, Becky; Solomon, Susan; Gettelman, Andrew; Battisti, David S.; Lin, Pu
Abstract: The Brewer‐Dobson circulation during the Last Glacial Maximum (LGM) is investigated in simulations using the Whole Atmosphere Community Climate Model version 6. We examine vertical mass fluxes, age of stratospheric air, and the transformed Eulerian mean stream function and find that the modeled annual‐mean Brewer‐Dobson circulation during the LGM is almost everywhere slower than that in the modern climate (with or without anthropogenic ozone depleting substances). Compared to the modern climate, the annual‐mean tropical upwelling in the LGM is 11.3–16.9%, 11.2–15.8%, and 4.4–10.2% weaker, respectively, at 100, 70, and 30 hPa. Simulated decreases in annual‐mean mass fluxes at 70 and 100 hPa are caused by a weaker parameterized orographic gravity wave drag and resolved wave drag, respectively. Plain Language Summary: The Brewer‐Dobson Circulation (BDC) is the large‐scale stratospheric circulation that transports stratospheric ozone from the tropics to poles and transports ozone from the stratosphere to troposphere in middle‐ and high‐latitudes. During the Last Glacial Maximum (LGM), the BDC could have been very different from the modern climate, due to different radiative constituent concentrations, the presence of large ice sheets in the Northern Hemisphere, and lower sea surface temperatures but an increased latitudinal sea surface temperature gradients. Here we investigate the BDC during the LGM using the Whole Atmosphere Community Climate Model version 6 with fully interactive chemistry for the first time. We find that the annual‐mean BDC during the LGM is everywhere weaker than that in the modern climate. A decreasing BDC in the LGM will have implications for the spatial distribution of ozone in the stratosphere, as well as stratosphere‐troposphere exchange and surface ultraviolet radiation. The latter two changes can be expected to affect tropospheric oxidant abundances, with potential implications for the lifetime of trace gases such as methane. Because of impacts on the climate sensitivity and methane, dynamically consistent O3 fields in the LGM from the present study provide an improved framework for an accurate simulation of the LGM climate. Key Points: A state‐of‐the‐art atmosphere model shows a slower Brewer‐Dobson circulation during the Last Glacial Maximum than the modern climate Compared to modern climate, the annual‐mean tropical upwelling in the Last Glacial Maximum is 14%, 14%, and 7% weaker at 100, 70, and 30 hPa, respectively Decrease in mass fluxes at 70 and 100 hPa is caused by weaker parameterized orographic gravity wave and resolved wave drags, respectively